Strategi kepala madrasah dalam menyiapkan peserta didik menghadapi asesmen nasional di MIN 1 Yogyakarta - Fitriyana Fitriyana; Subiyantoro Subiyantoro (Educatio, 2022)
In preparing the National Assessment/Assessment, the right strategy is needed from the head of the madrasa for the implementation of the assessment process so that students can follow the assessment process properly without any obstacles. The research that will be conducted aims to find out the strategies prepared by the madrasa head in preparing students to take part in the National Assessment (AN) at MIN 1 Yogyakarta. The method in this study uses a qualitative method with a descriptive approach. The data collection system is done through interviews, observation, and documentation. The data analysis technique uses the Miles Huberman data analysis model as quoted by Sugiyono which consists of 3 (three) related processes, namely data reduction, data presentation, and conclusion drawing/verification. Based on the research results, it can be seen that the National Assessment is designed to map the education system which will later be used as a reference for improving and evaluating the quality of education in each educational unit. Efforts made by the head of the madrasa to prepare students for the AKM (Minimum Competency Assessment) are by providing additional study hours and facilitating books to support the success of the program. However, the program cannot be fully implemented due to the pandemic. The supporting factors in the success of the National Assessment at MIN 1 Yogyakarta are the support and willingness of the madrasa head to be responsible and special supporting book facilities to be given to teachers and students of the National Assessment.